Whole Genome Sequencing of Single Circulating Tumor Cells Isolated by Applying a Pulsed Laser to Cell‐Capturing Microstructures. Issue 37 (26th June 2019) - Kim, Okju; Lee, Daewon; Chungwon Lee, Amos; Lee, Yongju; Bae, Hyung Jong; Lee, Han‐Byoel; Kim, Ryong Nam; Han, Wonshik; Kwon, Sunghoon
Abstract: Single cell analysis of heterogeneous circulating tumor cells (CTCs), by which the genomic profiles of rare single CTCs are connected to the clinical status of cancer patients, is crucial for understanding cancer metastasis and the clinical impact on patients. However, the heterogeneity in genotypes and phenotypes and rarity of CTCs have limited extensive single CTC genome research, further hindering clinical investigation. Despite recent efforts to build platforms that separate CTCs, the investigation on CTCs is difficult due to the lack of a retrieval process at the single cell level. In this study, laser‐induced isolation of microstructures on an optomechanically‐transferrable‐chip and sequencing (LIMO‐seq) is applied for whole genome sequencing of single CTCs. Also, the whole genome sequences and the molecular profiles of the isolated single cells from the whole blood of a breast cancer patient are analyzed. Abstract : Single circulating tumor cells (CTCs) within their protein expression contexts are analyzed through next generation sequencing for genome‐wide analysis. Whole blood from a metastatic breast cancer patient is processed through a microfluidic chip. CTCs are selected via fluorescence imaging and the fluorescently stained CTCs are isolated with a near‐infrared pulsed laser device in a noncontact manner.